The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep41293
|View full text |Cite
|
Sign up to set email alerts
|

A new serotonin 5-HT6 receptor antagonist with procognitive activity – Importance of a halogen bond interaction to stabilize the binding

Abstract: Serotonin 5-HT6 receptor has been proposed as a promising therapeutic target for cognition enhancement though the development of new antagonists is still needed to validate these molecules as a drug class for the treatment of Alzheimer’s disease and other pathologies associated with memory deficiency. As part of our efforts to target the 5-HT6 receptor, new benzimidazole-based compounds have been designed and synthesized. Site-directed mutagenesis and homology models show the importance of a halogen bond inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Molecular docking was performed to gain an insight into the binding mode of the library of compounds synthetized ( 5 – 26 ) to the recently developed 5-HT 6 R homology models [ 13 ] built on the β 2 adrenergic receptor template and optimized for the structures of Lead 1 and 2. The molecular docking indicated that newly synthesized compounds, generally, exhibited a very consistent binding mode with recently reported 5-HT 6 ligands [ 16 , 17 , 18 ]. An influence of the topology of aromatic substituents and the position of the 1,3,5-triazine substitution at the hydantoin ring on the binding has been observed ( Figure 2 ) and was in good agreement with results of the radioligand binding assay (see below).…”
Section: Resultssupporting
confidence: 65%
“…Molecular docking was performed to gain an insight into the binding mode of the library of compounds synthetized ( 5 – 26 ) to the recently developed 5-HT 6 R homology models [ 13 ] built on the β 2 adrenergic receptor template and optimized for the structures of Lead 1 and 2. The molecular docking indicated that newly synthesized compounds, generally, exhibited a very consistent binding mode with recently reported 5-HT 6 ligands [ 16 , 17 , 18 ]. An influence of the topology of aromatic substituents and the position of the 1,3,5-triazine substitution at the hydantoin ring on the binding has been observed ( Figure 2 ) and was in good agreement with results of the radioligand binding assay (see below).…”
Section: Resultssupporting
confidence: 65%
“…These studies also claim that 5-HT 6 R antagonists could improve cognitive functions; some agents are in the preclinical stage [74,75]. Many of these agents are associated with substantial improvements in different cognitive tasks and enhanced memory retention or formation in rodents [76]. To date, at least three candidates have already reached Phase II/III clinical trials as novel therapeutic agents for the treatment of AD [77].…”
Section: -Ht Receptorsmentioning
confidence: 99%
“…Indeed, the serotonin receptor 5-HT 6 R is an attractive drug target for reversing memory loss and learning disabilities associated with NDDs [77][78][79]. A recent study has discovered a new benzimidazole-based compound that is an antagonist of 5-HT 6 R and improves the novel object identification task in memory-deficit mice [76].…”
Section: -Ht Receptorsmentioning
confidence: 99%
“…[23][24][25]27,28 Based on docking study, it is postulated that it interacts with N6.55 and S5. 43 forming O-H/O and N-H/O bonds, 23,27,28 respectively. However, in the statistical approach applied for the majority of protein-ligand complexes deposited within the PDB (Protein Data Bank), the sulfonyl moiety is not involved in the strong hydrogen bond formation and usually occupies the hydrophobic pocket of the protein biding site.…”
Section: -21mentioning
confidence: 99%
“…[23][24][25][26][27][28] In the pharmacophore model of the 5-HT 6 R antagonists, the sulfonyl fragment is usually considered as the strong hydrogen bond acceptor. [23][24][25]27,28 Based on docking study, it is postulated that it interacts with N6.55 and S5. 43 forming O-H/O and N-H/O bonds, 23,27,28 respectively.…”
Section: -21mentioning
confidence: 99%